Pengaruh Kompetensi dan Employee Engagement terhadap Kinerja Karyawan dengan Iklim Organisasi sebagai Mediasi - Khairina, Shafira Qonita; Hidayatulloh, Furqon Syarief; Triyonggo, Yunus (IPB University, 2025)
This study aims to analyze the influence of competency and employee engagement on employee performance, with organizational climate as a mediating variable. The research was conducted at PT Great Giant Foods (GGF), focusing on the Agri Plantation Division. A quantitative approach was used, employing Structural Equation Modeling (SEM) as the method. A purposive sampling technique was applied to select 55 respondents based on their length of service and employment status. The results show that both competency and employee engagement have a positive and significant effect on organizational climate. However, neither has a significant direct effect on employee performance. Their indirect effects through organizational climate are also not significant. On the other hand, organizational climate has a positive and significant effect on employee performance. These findings emphasize the strategic role of organizational climate as a key factor in enhancing employee performance, particularly in contexts where operational support resources are limited. Therefore, human resource strategies should not only focus on improving individual competency and engagement but also on creating a supportive work environment.